“Watching Eyes” Triggers Third-Party Punishment: The Role of Emotion Within the Eyes - Li, Mingping; Shangguan, Chenyu; Shi, Huqing; Lu, Jiamei (Frontiers in Psychology, 2021)
Third-party punishment refers to a behavioral phenomenon whereby people punish wrongdoers even if their sanction incurs personal costs but yields no direct benefits. Given the eye cues demonstrated ability to convey signals of being observed, its effect on third-party punishment, driven by virtue of its effects on others’ perceptions, was investigated. In addition, emotional message featured in the eye region is crucial in social interaction, whether the emotion within the eyes serves this effect with varying degrees of influence has rarely considered. The present study aimed at exploring (a) the watching eyes effect on third-party punishment, and (b) whether this effect varies from negative eyes to positive eyes. By two experiments using a modified Third-Party Dictator Game, we displayed either eye images or control images above the question on whether to punish the dictators or not. There was no emotional diversity of eye cues in Experimental 1, and most participants tended to punish for unfair offer. However, the appearance of eye images increased the punishment relative to control images. In Experiment 2, the eye cues were subdivided into positive and negative. The effect of watching eyes on third-party punishment was significantly stronger when the eyes was negative rather than positive. Results revealed that eye cues play a role in promoting third-party punishment and offer potential insight into the mixed findings, such that the emotion within the eyes, and specifically the negative expression in the eyes, may influence the watching eyes effect.